The Impact Of Financial Leverage (Der), Return On Assets (Roa), And Inflation On Underpricing During Initial Public Offerings At The Indonesia Stock Exchange From 2019 To 2023 - Ade Restu Rukyah (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the effect of financial leverage, return on assets and inflation on underpricing in companies conducting Initial Public Offerings in companies listed on the IDX. The sample used in this study was 181 companies out of a total of 297 using purposive sampling, from the data obtained there were 61% of companies experiencing underpricing, this was caused by several factors, one of which was financial and non-financial factors which were used by both issuers and investors as benchmarks in determining stock price and investment decisions. The company's ability to return assets and debts is a factor that is generally considered by investors in investing in a company, in addition, the ongoing inflation rate is another factor that can reduce the real value of the company's income and profits in the future, making investors demand a high safety margin which results in the company setting a lower IPO price. Therefore, ROA, financial leverage and inflation were chosen as dependent variables in this study. The research method used is quantitative. Based on the research results obtained, financial factors, namely financial leverage and ROA, do not have a significant effect on underpricing, with a p-value of 0.554 and 0.397, while non-financial factors, namely inflation, have a significant effect on underpricing with a p-value of 0.000 <0.05.